The Development of Catalytic Nucleophilic Additions of Terminal Alkynes in Water - Li, Chao-Jun (Accounts of chemical research, 2010)
One of the major research endeavors in synthetic chemistry over the past two decades is the exploration of synthetic methods that work under ambient atmosphere with benign solvents, that maximize atom utilization, and that directly transform natural resources, such as renewable biomass, from their native states into useful chemical products, thus avoiding the need for protecting groups. The nucleophilic addition of terminal alkynes to various unsaturated electrophiles is a classical (textbook) reaction in organic chemistry, allowing the formation of a C−C bond while simultaneously introducing the alkyne functionality. A prerequisite of this classical reaction is the stoichiometric generation of highly reactive metal acetylides. Over the past decade, our laboratory and others have been exploring an alternative, the catalytic and direct nucleophilic addition of terminal alkynes to unsaturated electrophiles in water. We found that various terminal alkynes can react efficiently with a wide range of such electrophiles in water (or organic solvent) in the presence of simple and readily available catalysts, such as copper, silver, gold, iron, palladium, and others. In this Account, we describe the development of these synthetic methods, focusing primarily on results from our laboratory. Our studies include the following: (i) catalytic reaction of terminal alkynes with acid chloride, (ii) catalytic addition of terminal alkynes to aldehydes and ketones, (iii) catalytic addition of alkynes to CN bonds, and (iv) catalytic conjugate additions. Most importantly, these reactions can tolerate various functional groups and, in many cases, perform better in water than in organic solvents, clearly defying classical reactivities predicated on the relative acidities of water, alcohols, and terminal alkynes. We further discuss multicomponent and enantioselective reactions that were developed. These methods provide an alternative to the traditional requirement of separate steps in classical alkyne reactions, including the pregeneration of metal acetylides with stoichiometric, highly basic reagents and the preprotection of sensitive functional groups. Accordingly, these techniques have greatly enhanced overall synthetic efficiencies and furthered our long-term objective of developing Grignard-type reactions in water.